2019
DOI: 10.15171/jcs.2019.014
|View full text |Cite
|
Sign up to set email alerts
|

Infertile Couples' Needs after Unsuccessful Fertility Treatment: a Qualitative Study

Abstract: Introduction: Infertility is a major medical issue. Investigations and treatment of infertility are the beginning of a complex, time-consuming and stressful process for couples that may fail well. The present study explored the needs of infertile couples following treatment failure with Assisted Reproductive Technologies (ARTs). Methods: A descriptive qualitative study was conducted in an Iranian infertility center, in the Northeast of the country between April 2016 and June 2017. The researchers recruited 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…The authors concluded that low response to treatment indicates that couples need no group counseling and psychotherapeutic treatment in the first IVF cycle. By contrast, this result was not consistent with the findings of Zarghami et al [ 49 ], Yeylagh Beigi et al [ 8 ], Likhachov et al [ 50 ], and Joelsson et al [ 51 ]. These contradictory results can be attributed to the difference in sample size and measurement tools.…”
Section: Discussioncontrasting
confidence: 86%
“…The authors concluded that low response to treatment indicates that couples need no group counseling and psychotherapeutic treatment in the first IVF cycle. By contrast, this result was not consistent with the findings of Zarghami et al [ 49 ], Yeylagh Beigi et al [ 8 ], Likhachov et al [ 50 ], and Joelsson et al [ 51 ]. These contradictory results can be attributed to the difference in sample size and measurement tools.…”
Section: Discussioncontrasting
confidence: 86%
“…(2019a, 2019b). [ 25 26 ] The only difference between the needs found in the current study was the needs which was specific for the CAM consumption in infertile women including the needs to “integration of CAM with conventional medicine in treatment of infertility” and “the need for CAM use counseling”. Educational and informational needs were also mentioned in previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with the findings of the current study, the need for psychological counseling about infertile women is an important issue, which has been addressed in studies of Ebrahimzadeh Zagami et al . (2019a, 2019b),[ 25 26 ] Latifnejad Roudsari (2017),[ 59 ] Taghipour et al . (2020),[ 60 ] Hosseinpanahi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internationally, when infertility treatment fails, the blame may be mainly on women (Tabong & Adongo, 2013) and infertile women may experience negative social interactions such as insensitive remarks and inappropriate support from friends and family (Akizuki & Kai, 2008). In Iran, the patriarchal culture of the society also shifts the blame onto women in cases of infertility treatment failure, however, at the same time, by shifting it away from men, it ignores women's distress and emotional reactions to unsuccessful treatment (Ebrahimzadeh et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%